Influence of Religiosity, Service Quality, Customer Intimacy and Imagetocustomer Loyaltywithtrustas Mediation In Indonesian Syariah Bank In Bengkulu - Andesta, Nara; Eka Putri, Seprianti (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the effect of religiosity, service quality, brand image, customer intimacy on customer loyalty mediated by trust. The research method is quantitative, and the primary data is collected through an online questionnaire. Participants in this survey consisted of 173 Indonesian Islamic bank customer respondents. The analytical method in this survey uses SmartPLS Version 4.2.9.2 analysis to filter and analyze data. The results of the study show that (1) Brand image has a positive and significant effect on customer loyalty; (2) Brand image has a positive and significant effect on trust (3) Customer intimacy has a positive and significant effect on customers (4) Religiosity has a positive and significant effect on customer loyalty (5) Religiosity has a positive and significant effect on trust (6) Service Quality has a positive and significant effect on customers (7) Service Quality has a positive and significant effect on (8) Trust has a positive and significant effect on customer loyalty (9) Religiosity has a positive and significant effect on customer loyalty through trust. (10) Service quality has a positive and significant effect on customer loyalty through trust. (11) brand image has a positive and significant effect on customer loyalty through trust